2-[(1,3-Benzothiazol-2-yl)iminomethyl]-4-bromophenol - Diao, Hai-Peng (International Union of Crystallography, 2011)
In the title compound, C(14)H(9)BrN(2)OS, the dihedral angle between the benzene rings is 3.1 (3)°. An intramolecular O—H⋯N(imine) hydrogen bond occurs. The crystal structure is stabilized by weak intermolecular C—H⋯O interactions.